Circulating mRNA signature as a marker for high-risk prostate cancer. (13th July 2019) - De Souza, Marilesia Ferreira; Kuasne, Hellen; Barros-Filho, Mateus De Camargo; Cilião, Heloísa Lizotti; Marchi, Fabio Albuquerque; Fuganti, Paulo Emilio; Rogatto, Silvia Regina; Cólus, Ilce Mara De Syllos
Abstract: Prostate cancer (PCa) is the second most common cancer in men. The indolent course of the disease makes the treatment choice a challenge for physicians and patients. In this study, a minimally invasive method was used to evaluate the potential of molecular markers in identifying patients with aggressive disease. Cell-free plasma samples from 60 PCa patients collected before radical prostatectomy were used to evaluate the levels of expression of eight genes ( AMACR, BCL2, NKX3-1, GOLM1, OR51E2, PCA3, SIM2 and TRPM8 ) by quantitative real-time PCR. Overexpression of A MACR, GOLM1, TRPM8 and NKX3-1 genes was significantly associated with aggressive disease characteristics, including extracapsular extension, tumor stage and vesicular seminal invasion. A trio of genes ( GOLM1, NKX3-1 and TRPM8 ) was able to identify high-risk PCa cases (85% of sensitivity and 58% of specificity), yielding a better overall performance compared with the biopsy Gleason score and prostate-specific antigen, routinely used in the clinical practice. Although more studies are required, these circulating markers have the potential to be used as an additional test to improve the diagnosis and treatment decision of high-risk PCa patients. Abstract : The levels of expression of eight cell-free circulating messenger RNAs were evaluated in plasma samples from prostate cancer patients. Three of them, GOLM1, NKX3-1 and TRPM8, have the potential to identify high-risk prostate cancer.